2022
DOI: 10.1186/s13007-022-00878-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid monitoring of flavonoid content in sweet tea (Lithocarpus litseifolius (Hance) Chun) leaves using NIR spectroscopy

Abstract: Background Sweet tea, which functions as tea, sugar and medicine, was listed as a new food resource in 2017. Flavonoids are the main medicinal components in sweet tea and have significant pharmacological activities. Therefore, the quality of sweet tea is related to the content of flavonoids. Flavonoid content in plants is normally determined by time-consuming and expensive chemical analyses. The aim of this study was to develop a methodology to measure three constituents of flavonoids, namely, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Tian et al [57] developed an NIR model to predict three flavonoid components (total flavonoids, phloridin, and trilobatin) in sweet tea leaves. The R 2 values of the NIR models were 0.967 for calibration, 0.858 for validation, and 0.818 for prediction sets, indicating the rapid and convenient ability of NIR to determine flavonoid content in sweet tea.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al [57] developed an NIR model to predict three flavonoid components (total flavonoids, phloridin, and trilobatin) in sweet tea leaves. The R 2 values of the NIR models were 0.967 for calibration, 0.858 for validation, and 0.818 for prediction sets, indicating the rapid and convenient ability of NIR to determine flavonoid content in sweet tea.…”
Section: Introductionmentioning
confidence: 99%
“…Vis/NIR spectroscopy has been used to make prediction model for natural pigments in agricultural products. Several studies also revealed that spectroscopy technology has succeeded in predicting the content of flavonoids [ 29 , 30 ] and carotenoids [ 31 , 32 ]. Furthermore, previous studies have compared predictions based on color and spectra together.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, Tian et al [28] developed an NIR model to predict three components of flavonoids (total flavonoids, phloridin, and trilobatin) in sweet tea leaves, as an alternative to time-consuming and expensive chemical analyses. The R 2 for all calibration, validation, and prediction sets of the NIR PLS models were 0.967, 0.858, and 0.818, respectively.…”
Section: Introductionmentioning
confidence: 99%